Simulation of Nonpolar p-GaN/i-N/n-GaN Solar Cells - Ming-Jer Jeng (International Journal of Photoenergy, 2012)
It is well known that nitride-based devices suffer the polarization effects. A promising way to overcome the polarization effects is growth in a direction perpendicular to the c-axis (nonpolar direction). Nonpolar devices do not suffer polarization charge, and then they have a chance to achieve the high solar efficiency. The understanding of the solar performance of non-polar InGaN-based solar cells will be interesting. For a pin non-polar solar cell with GaN p- and n-cladding layers, the conduction band offset (or barrier height, ) between an intrinsic layer and n-GaN layer is an important issue correlating to the efficiency and fill factor. The efficiency and fill factor will be seriously degraded due to sufficiently high barrier height. To reduce a high barrier height, some graded layers with an energy bandgap between the energy bandgap of n-GaN and InxGa1−xN intrinsic layer can be inserted to the interface of n-GaN and InxGa1-xN layers. From simulation, it indicates that the insertion of graded layer is an effective method to lower energy barrier when there exists a high energy band offset in non-polar nitride devices.